CircRNA_000864 Upregulates B-cell Translocation Gene 2 Expression and Represses Migration and Invasion in Pancreatic Cancer Cells by Binding to miR-361-3p - Huang, Linsheng; Han, Junxiang; Yu, Huifan; Liu, Jialing; Gui, Lili; Wu, Zhengkun; Zhao, Xinxu; Su, Shiqi; Fu, Gaohang; Li, Fei (Frontiers in Oncology, 2020)
Background: Pancreatic cancer is a fatal disease with a very poor prognosis due to its characteristic insidious symptoms, early metastasis and chemoresistance. Circular RNAs (circRNAs) are involved in the development of pancreatic cancer. Aims: Hence, the aim of this study is to elucidate the mechanism of circRNA_000864 in regulating BTG2 expression in pancreatic cancer by binding to miR-361-3p. Methods: CircRNA_000864, miR-361-3p, and BTG2 expression patterns in the pancreatic cancer tissues were detected by RT-qPCR. Correlation among circRNA_000864, miR-361-3p, and BTG2 was evaluated by RNA-pull down assay, RIP assay, and dual luciferase reporter gene assay. After ectopic expression and depletion experiments, EdU assay, Transwell assay, and flow cytometry were employed to assess the cell proliferation, migration and invasion, and cell cycle, and apoptosis. Xenotransplantation of nude mice was conducted to detect the effects of circRNA_000864, miR-361-3p and BTG2 on tumor growth. Results: CircRNA_000864 and BTG2 were poorly expressed and miR-361-3p was highly expressed in the pancreatic cancer tissues. CircRNA_000864 bound to miR-361-3p could target BTG2. Cell proliferation, migration, and invasion were inhibited, and the cell cycle arrest and apoptosis were stimulated after overexpression of circRNA_000864 or BTG2 or downregulation of miR-361-3p. Overexpression of circRNA_000864 or downregulation of miR-361-3p also decreased the tumor growth in vivo. Conclusions: Conjointly, our findings elicited that the overexpression of circRNA_000864 could promote BTG2 expression to inhibit pancreatic cancer development by binding to miR-361-3p, which represents an appealing therapeutic target for the treatment of pancreatic cancer.